2014
DOI: 10.4012/dmj.2013-223
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT and histologic analyses of bone surrounding immediately loaded miniscrew implants: Comparing compression and tension loading

Abstract: This study investigated the effect of immediate force on bone adaptations surrounding miniscrew implants. Ten miniscrew implants were placed on the mandibles in three beagle dogs. Five pairs of miniscrew implants were immediately loaded with 150 g of continuous force using nickel-titanium coil springs for 8 weeks. The values of bone mineral density (BMD), bone mineral content (BMC), and bone volume (BV) of cortical and trabecular bone for compression loading and tension loading were obtained by µCT analysis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Broadly, a trend for an increased remodeling on the compression side has been determined when the differences were reported between the two sides [54,55] and attributed to a specific range of the applied force magnitude and biological response of the deformed bone [56]. More recent reports, in line with the data obtained in this study, identified no significant differences in the bone parameters, between tension or compression regions submitted to a functional orthodontic load [57,58]. It is possible that the obtained differences may relate to variations within the experimental design, including dissimilarities in the selected animal model, the characteristics of the used mini-implants, the force and loading protocols, the location of implantation, the period of evaluation, the methodology, and the characterization methodologies, among other variables.…”
Section: Resultssupporting
confidence: 76%
“…Broadly, a trend for an increased remodeling on the compression side has been determined when the differences were reported between the two sides [54,55] and attributed to a specific range of the applied force magnitude and biological response of the deformed bone [56]. More recent reports, in line with the data obtained in this study, identified no significant differences in the bone parameters, between tension or compression regions submitted to a functional orthodontic load [57,58]. It is possible that the obtained differences may relate to variations within the experimental design, including dissimilarities in the selected animal model, the characteristics of the used mini-implants, the force and loading protocols, the location of implantation, the period of evaluation, the methodology, and the characterization methodologies, among other variables.…”
Section: Resultssupporting
confidence: 76%
“…Nakagaki et al (44) observed that the bone mineralization of the compression region of cortical bone surrounding immediately loaded miniscrews was significantly higher than that of the tension region, while the bone-to-implant contact amount was approximately the same, and they concluded that immediate loading does not inhibit osseointegration of miniscrew implants but may stimulate bone mineralization, which would explain why immediate loading could contribute to maintain a higher torque value in the early phases. (II) Significant miniscrew MIT differences existed in miniscrew locations according to the placement times, even though the trend of MIT mean in mandibular and maxillary arch according to placement time seemed like similar in two groups ( Supplementary Figure 1).…”
Section: Main Findings and Interpretationmentioning
confidence: 99%
“…The absolute values of the principal strains are used in this expression so that there is no distinction made between positive and negative values of principal strains on the change in accumulated strain. For bone, both f B,I ε I,N and f B,I I ε I I,N are needed to describe bone tissue evolution in tension and compression [19,67,91] while for cartilage and fibrous tissue, only f C,I I ε I I,N and f F,I ε I,N are used [13,14].…”
Section: Modeling Of the Mechanostatmentioning
confidence: 99%